165 Activating antigen carriers generated with microfluidics cell squeezing drive effective anti-tumor responses. (9th November 2020) - Blagovic, Katarina; Ramakrishnan, Amritha; Sharei, Armon; Bernstein, Howard; Seidl, Katherine; Yarar, Defne
Abstract : Background: Activation of T cell responses is essential for effective tumor clearance, however generating targeted, effective antigen presentation to stimulate T cell response remains challenging. We can harness the natural process of red blood cell (RBC) clearance from the body to activate the antigen-specific immune responses. Using the Cell Squeeze® microfluidics platform, we generate activating antigen carriers (AACs) from RBCs to drive antigen presentation and T cell activation in human and murine models. Methods: We loaded proteins or synthetic long peptide antigens together with adjuvants into murine or human RBCs with Cell Squeeze® (SQZ'ing) to generate AACs and investigated the effects of SQZ'ing on the RBC membrane. Following intravenous AAC injection into mice, we measured AAC clearance kinetics and characterized the site and cell type of AAC uptake. We investigated the regulation of activation markers on phagocytes that engulf AACs, clearance of endogenous RBCs in mice treated with AACs, and the effect of boosting with AACs on endogenous T cell responses. To determine the ability of AACs to control subcutaneously implanted tumors, we measured tumor growth rates in mice therapeutically treated and boosted with AACs. Finally, we observed in vitro uptake of human AACs loaded with adjuvant and resultant maturation of monocyte-derived dendritic cells (MODCs) to qualify adjuvant delivery. Peptide antigen delivery to human AACs was measured with flow cytometry and fluorescence microscopy. Results: We demonstrated that SQZ'ing effectively loads AACs without reducing CD47 expression. When administered into a mouse, AACs were cleared from circulation within one hour and were engulfed by professional phagocytes in both the spleen and liver. In vivo, AACs upregulated activation markers on macrophages and DCs, and administration of AACs does not affect clearance or half-life of endogenous RBCs. Therapeutic AAC administration to mice strongly impedes tumor growth and extends survival; the anti-tumor responses correlate with >10x increase in antigen-specific CD8+ tumor-infiltrating lymphocytes compared to untreated mice. Boosting enhances endogenous T cell responses and boosting at early time points in the tumor model enhances low dose vaccinations. In an in vitro human system, we demonstrated that human AACs can be loaded with peptide antigen and adjuvant such that upon engulfment, AACs stimulated MODC maturation. Conclusions: In summary, these results indicate that AACs loaded with antigen and adjuvant can effectively drive antigen presentation and prime a potent anti-tumor response in mice. These data support the further study of SQZ AACs as an immunotherapy for cancer treatment. Ethics Approval: All methods were performed in accordance with the relevant guidelines and regulations. Animal studies were approved by the Institutional Animal Care and Use Committee (IACUC) at SQZ Biotechnologies, using the recommendations from the Guide for the Care and Use of Laboratory Animals of the National Institutes of Health and the Office of Laboratory Animal Welfare. All activities were also conducted in accordance with Public Health Service (PHS) Policy on Humane Use and Care of Laboratory Animals.